2020
DOI: 10.5334/cie.7
|View full text |Cite
|
Sign up to set email alerts
|

Levelling Education Outcomes for Students With Medical and Mental Health Needs

Abstract: Students' educational and behavioural outcomes can be adversely impacted by the unique challenges posed by chronic health conditions. As some children and adolescents may live with these challenges throughout their education, hospital-based educators play a crucial role in reducing the impacts of health conditions on educational outcomes. This study assessed the extent to which the support provided by the School of Special Educational Needs: Medical and Mental Health (SSEN:MMH, Western Australia) attenuated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…The back-to-school transition and schooling at home have been identified as phases associated with increased stress (McLoone et al, 2011;Wakefield et al, 2009), and again suggests that more support for families and communication across systems is necessary. This finding is also consistent with a recent Australian study showing that most students with chronic health conditions missed more school time than the support service could respond to in terms of making up for lost learning, with many students missing over 40 days of school in a year but receiving teaching support equivalent to less than 2 days of school (Cave et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The back-to-school transition and schooling at home have been identified as phases associated with increased stress (McLoone et al, 2011;Wakefield et al, 2009), and again suggests that more support for families and communication across systems is necessary. This finding is also consistent with a recent Australian study showing that most students with chronic health conditions missed more school time than the support service could respond to in terms of making up for lost learning, with many students missing over 40 days of school in a year but receiving teaching support equivalent to less than 2 days of school (Cave et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…These parents were motivated to participate and may have placed greater focus on education. Thus, recent findings showed that high-achieving students with chronic health conditions were more likely to opt into receiving support from special education support services ( Cave et al, 2020 ). Experiences also pertain largely to the early schooling years.…”
Section: Discussionmentioning
confidence: 99%
“…Students with medical conditions have the right to the most comprehensive education possible, which includes regular attendance, engagement in all social and broader areas of school life, and participation in courses whenever possible. Because healthy students are better when it comes to learning, an increase in student engagement, reaching of academic potentials and the closing of achievement gaps are attained when positive environments are instituted to ensure healthy and well-prepared students (Cave et al, 2020).…”
Section: Introductionmentioning
confidence: 99%